The relationship between early musical training and executive functions: Validation of effects of the sensitive period. (January 2022) - Chen, Jiejia; Scheller, Meike; Wu, Chuanyu; Hu, Biyu; Peng, Rong; Liu, Cuihong; Liu, Siyong; Zhu, Liwen; Chen, Jie
Interest in the influence of musical training on executive functions (EFs) has been growing in recent years. However, the relationship between musical training and EFs remains unclear. By dividing EFs into inhibitory control, working memory, and cognitive flexibility, this study systematically examined its association with musical training in children, and further verified whether there was a sensitive period for the influence of music training on EFs. In Experiment 1, musically trained and untrained children were asked to complete the Go/No-go, Stroop, Continuous Performance, and Switching tasks. Results showed that musically trained children had an advantage in attention inhibition, response inhibition, and working memory, but not in cognitive flexibility. Moreover, the level of musical training was positively correlated with response inhibition and working memory abilities. In Experiment 2, results showed that early-trained musicians performed better on measures of attention inhibition, response inhibition, and working memory than did the age-matched control group, but late-trained musicians only performed better in attention inhibition. Thus, our findings suggest that music training is associated with enhanced EF abilities and provide the first evidence that early childhood is a sensitive period when musical training has a more powerful effect on the development of EFs.